2020
DOI: 10.1111/mec.15573
|View full text |Cite
|
Sign up to set email alerts
|

Expanding host specificity and pathogen sharing beyond viruses

Abstract: Most emerging pathogens of humans can infect multiple host species (Woolhouse & Gowtage‐Sequeria, 2005). This simple fact has motivated multiple large‐scale, comparative analyses of the drivers of pathogen sharing and zoonotic pathogen richness among hosts as well as the factors determining the zoonotic potential of pathogens themselves. However, most of this work focuses on viruses, limiting a broader understanding of how host range varies within and between pathogen groups. In this issue of Molecular Ecology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Evaluating human disease risk from zoonotic pathogens, those shared between wildlife and humans, requires characterization of pathogen traits influencing their environmental distribution and spillover potential (Sánchez et al 2021). Recent meta-analyses and reviews have repeatedly identified host breadth, or the capacity to infect phylogenetically diverse species, as a key trait influencing spillover (Woolhouse & Gowtage-Sequeria 2005;Olival et al 2017;Becker & Albery 2020). Greater host breadth provides pathogens more opportunities for population persistence across heterogeneous environments (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating human disease risk from zoonotic pathogens, those shared between wildlife and humans, requires characterization of pathogen traits influencing their environmental distribution and spillover potential (Sánchez et al 2021). Recent meta-analyses and reviews have repeatedly identified host breadth, or the capacity to infect phylogenetically diverse species, as a key trait influencing spillover (Woolhouse & Gowtage-Sequeria 2005;Olival et al 2017;Becker & Albery 2020). Greater host breadth provides pathogens more opportunities for population persistence across heterogeneous environments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analyses and reviews have repeatedly identified host breadth, or the capacity to infect phylogenetically diverse species, as a key trait influencing spillover (Woolhouse & Gowtage-Sequeria 2005; Olival et al . 2017; Becker & Albery 2020). Greater host breadth provides pathogens more opportunities for population persistence across heterogeneous environments (e.g.…”
Section: Introductionmentioning
confidence: 99%